(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
This study is aimed at investigating the product gas yield and composition of EFB briquettes gasification using a simplified stoichiometric equilibrium model. Similar mathematical models have been successfully adopted by a number of research groups to investigate the thermochemical conversion of biomass species. Hence the effect of gasification temperature on the product gas yield and composition of EFB briquettes gasification using a simplified stoichiometric equilibrium model is presented in this study. The results indicate that the H2 and CO content increased with increasing temperature from 600 to 800Â°C while the CO2, N2 and CH4 content decreased. The H2 content increased with increasing temperature, with peak production of 25.55 mol % at 750Â°C. The HHV (4.87 to 8.38 MJ/Nm3), CGE (27.72 to 47.71%) and CCE (25.42 to 41.54%) values increased with increasing temperature during gasification. Hence for a reacting system with known reaction mechanism, the model can be used to reasonably deduce the yield and composition of the gasification products.Â